A case for a national registry of red blood cell antibodies. Issue 5 (12th January 2022) - Mathur, Gagan; Wilkinson, Matthew B.; Island, Eddie R.; Menitove, Jay E.; Tilzer, Lowell
Abstract: Background and Objectives: Red blood cell (RBC) antibody levels diminish over time and negative antibody screen are commonly seen in patients with a history of antibodies. Most hospitals do not have access to a shared registry of antibodies previously detected at other hospitals. Materials and Methods: We describe a case where the patient was found to be at high risk of bleeding during liver transplantation. Antibody screen on admission was negative but a history of anti‐Jk a was identified on reviewing patient's history in local registry of RBC antibodies. The surgery was pushed back to arrange for antigen‐negative units. The patient received a total of 16 Jk(a−) RBC units during the admission. Results: No acute or delayed transfusion adverse reactions were seen. However, if the history of anti‐Jk a identified at another local hospital was not known, approximately three‐quarters of the units transfused would have been Jk(a+). Transfusing Jk(a+) units could have potentially exposed the patient to risk of developing an acute and/or delayed haemolytic transfusion reaction which could have led to significant morbidity and perhaps mortality. Conclusion: With this case report, we build a case for developing a national registry of RBC antibodies to help improve patient safety and outcomes.